Revisiting Roel Meijer's Typology of Salafism: A Critical Reading of the Salafi Movement Studies - Azzam Musoffa (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to review the typology of Salafists introduced by Roel Meijer in his work